An Inverted Management Strategy for the Fishery of Endangered Marine Species - Pinheiro, Hudson T.; Nunes, Jose A. C. C.; Coni, E. O. C.; Almeida, E. C. G.; Sampaio, C. L. S.; Ferreira, Carlos E. L.; Meirelles, Pedro M.; Hostim-Silva, M.; Pereira, Pedro H. C.; Giglio, Vinicius J.; Gasparini, J. L.; Rocha, L. A.; et al. (Frontiers in Marine Science, 2021)
Overfishing is notorious for triggering population collapses and disrupting marine biological functioning worldwide. To counter such a threat, policy-makers have created and implemented multiple management strategies, but most were incapable to prevent the decline of several key species. Here, we discuss a new management strategy in force since June 2019 in Brazil that aims to deter the overfishing of parrotfish species of the genera Scarus and Sparisoma. This innovative strategy, here referred to as inverted management, allows the capture of endangered parrotfish species inside management areas, such as partially protected marine areas—MPAs, but bans it elsewhere. This initiative is supposed to be built in a partnership among the government, scientists, managers, and fishers. If implemented correctly, endangered species would recover in the much larger area outside MPAs, and fishers would benefit from the conservation-value of the scarce and valued product. However, to succeed, the strategy depends on the adoption of a series of challenging management rules that are not currently being enforced along an extensive coastline. So far, few MPAs have incorporated rules for endangered species in their management plan, and those that have done so have no plans or the means to enforce them. Therefore, fishing of endangered species is currently ongoing without any management or monitoring in the entire Brazilian coast. Concerned with the challenges to develop plans to recover populations of endangered species faced by Brazilian managers, we suggest wide communication and a ban on the fisheries until management plans are implemented. Additionally, we suggest that the effectiveness of the inverted management strategy for parrotfishes should be assessed before it’s applied to other endangered species.